DISCOVERY LEARNING IN REAL CLASSROOMS: VIEWS ON CRITICAL THINKING AND COLLABORATION - Ela Yulastini; Eka Sastrawati; Atri Widowati (El Midad, 2026)
This study aims to explore the effectiveness of Discovery Learning in fostering students’ critical thinking and collaboration skills in IPAS learning at the elementary school level. The research employed a mixed-methods approach with a convergent exploratory design, involving one Grade V IPAS teacher and 21 students at a public elementary school in Muaro Jambi Regency. Quantitative data were collected through a Likert-scale questionnaire, while qualitative data were obtained from interviews and learning documentation. The data were analyzed descriptively and thematically and then integrated using a joint display technique. The results indicate that the teacher perceived the implementation of Discovery Learning as very effective in developing critical thinking (87%) and collaboration skills (85%). In comparison, students’ perceptions were categorized as good, with an average score of 81%, and the lowest achievement was in the information evaluation aspect (75%). These findings imply that Discovery Learning can support the development of critical thinking and collaboration skills in elementary IPAS learning when appropriately scaffolded and effectively facilitated by teachers.